Learning preferences of undergraduate dental students using VARK analysis - Shrestha, Ashish; Marla, Vinay; Shrestha, Sushmita; Rimal, Jyotsna (Journal of Kathmandu Medical College, 2020)
Background: Learning preference is a complex character in which learners most efficiently perceive, process, store, and recall what they are learning. Objectives: This study was conducted with an objective to identify the preferred learning styles of undergraduate dental students such that suitable modification in the teaching learning environment could be made. Methodology: An analytical cross-sectional study was carried at B.P. Koirala Institute of Health Sciences, Nepal among undergraduate dental students from June to December 2019 after getting ethical approval. Convenience sampling method was used to include all undergraduate students from first to final year; of which 252 provided consent. VARK questionnaire (version 7.8) comprising 16 multiple choice questions were used to analyse the learning preferences and were accordingly categorised for further statistical analysis. Results: Out of 280 students, a total of 252 students (90%; 90 males, 162 females) responded to the questionnaire among whom 89 (35.3%) had uni-modal learning preferences. Of the total, 55 (21.8%) had bi-modal, 39 (15.4%) had tri-modal, and 69 (27.3%) had quadri-modal learning preferences. Among the uni-modal preferences, ’K mild’ was most common (36, 14.3%) followed by ’A mild’. Among bi-modal learning preferences ’AK type’ (35, 13.9%) was most common and VAK type was common among tri-modal learning preferences. ’VARK type two’ (33, 13.1%) was common quadri-modal learning preferences. Conclusion: This study highlighted the variations in learning preferences among dental students suggesting the need for a flexible learning environment. Understanding learning preferences can help to plan lessons effectively and help to manage students in a better way.